Ocular size and shape in lens-induced myopization in young Guinea pigs - Dong, Li; Jonas, Jost B. (BMC ophthalmology, 2019)
Lens-induced myopization in guinea pigs has been used as model for the process of myopization in humans. It has not been explored yet whether the change in globe shape in eyes undergoing myopization is similar in experimental myopia in guinea pigs and in clinical myopia in patients.
Gesehen am 09.03.2020